PWE-069 Comparison Of Microwave With Monopolar And Bipolar Coagulation In A Porcine Model. (9th June 2014) - Tsiamoulos, ZP; Hancock, C; Sibbons, PD; Saunders, BP
Abstract : Introduction: Intra-procedural bleeding is considered an immediate serious adverse event and a major concern for the endoscopist and the patient. Current endoscopic devices utilise monopolar or bipolar energy to treat acute bleeding vessels and/or pre-coagulate visible vessels but there are no ex vivo comparative studies assessing the safety profile with histology. Methods: The optimal time of application for the microwave modality of a new endoscopic device "Speedboat-RS2, Creo Medical Ltd, UK" was initially assessed compared to a standard mono-polar endoscopic device, Coagrasper, Olympus, USA. After histological assessment of the optimal time range, a comparison of the Speedboat RS2 to a standard bipolar endoscopic device, Gold Probe, Boston Scientific, USA, and to standard monopolar device, Coagrasper, was performed to assess the safety profile of coagulation with histology and the endoscopic performance of pre-coagulation in the porcine colon. The Speedboat-RS2 blade delivered microwave coagulation (5.8 GHz) for hemostasis. The following parameters were measured in 3 female pigs: histological assessment and pre-coagulation endoscopic performance. All animals were recovered for 2, 5 and 7days. Results: In animal one, microwave bursts of 5, 10 and 15 sec were applied to the revealed submucosa compared to standard monopolar bursts of a 1 sec. Histology showed that 5 and 10 sec of microwave has equivalent histological appearance with standard monolopar preserving the serosal integrity with mild muscle alteration. In animal 2 and 3, microwave was applied for 9 sec in 6 lesions, standard monopolar was applied for 1–2 sec in 6 lesions and standard bipolar was applied for 3–4 sec in 6 more lesions. Histology showed viable serosa with no muscle alterations in microwave group, viable serosa with mild muscle alterations in standard bipolar and viable serosa with mild/moderate muscle alterations in standard monopolar group. In all cases muscle layer cells were contiguous. During the pre-coagulations endoscopic assessment, all modalities were applied to coagulate vessels with median calibre of 2 mm before and after dissection. Effective pre-coagulation was achieved in 3 out of the 6 visible vessels (microwave group) and in 2 out of the 6 visible vessels (standard monopolar and bipolar groups). Effective coagulation (defined when blood flow stopped) was achieved after the dissection, in all three groups. Conclusion: Compared to Coagrasper (monopolar) and Gold Probe (bipolar), the microwave modality of Speedboat RS2 appears to be equivalent during the pre-coagulation phase. The safety profile of coagulation phase resembles the profile of the other two modalities but with less muscle alterations in the histological specimens. Disclosure of Interest: Z. Tsiamoulos Consultant for: Creo Medical Ltd, C. Hancock Shareholder of: Creo Medical Ltd, P. Sibbons Paid instructor for: Creo Medical Ltd, B. Saunders Consultant for: Creo Medical Ltd, Paid instructor for: Olympus KeyMed.